ANALISA STRATEGI PENJUALAN PADA PT. LION SUPER INDO JAKARTA UTARA - Umi Hanik Makmuroh; Mira Firlana (POLITEKNIK LP3I JAKARTA, 2025)
This study uses a qualitative descriptive research method with data collection techniques through interviews, observations and literature studies. The purpose of this study is to analyze the Sales Strategy at PT. Lion Super Indo using SWOT analysis. The results of the study show that the sales strategy at PT. Lion Super Indo's sales activities are known to carry out marketing mix activities ranging from products, prices, places and promotions. Sales are integrated activities to develop strategic plans that are directed at efforts to satisfy the needs and desires of buyers/consumers, in order to get sales that generate profits or benefits. Customers who still want to redeem cheaply even though they do not shop according to the requirements can join with other customers whose nominal purchases reach or exceed Rp. 120,000 and for member applications that are error can restart the cellphone. The company can make an introduction to the application to the public in the form of a special small brochure containing a barcode and create ideas for holding a lottery.